Sociocultural dimensions of South Sudanese refugees’ resettlement experiences in Australia : Cultural and linguistic capital - Woul, GAK (International Journal of Language and Literary Studies, 2025)
This article explores the sociocultural dimensions of the resettlement experiences of South Sudanese refugees in Australia from 2000 to 2010. The findings are drawn from a series of semi-structured interviews that investigated three key themes: employment experiences, the impact of Australian news media, and the influence of gender and gendered practices. The analysis utilizes Bourdieu’s concepts of social, cultural, and linguistic capital to understand the participants’ narratives. The article highlights the challenges the participants faced in gaining employment due to lack of recognition of their overseas qualifications, as well as the negative portrayal of South Sudanese youth in the Australian media. It also examines how traditional gender roles and the value placed on male education in South Sudan shaped the participants’ experiences of resettlement in Australia. The article concludes by discussing the implications of these findings for supporting the successful integration of refugee communities.